The non-canonical mitochondrial inner membrane presequence translocase of trypanosomatids contains two essential rhomboid-like proteins - Anke Harsman (Nature Portfolio, 2016)
The mitochondrial protein import machinery is crucial for eukaryotes but little is known about its evolutionary origin. Here, the authors characterize the translocase of the inner membrane (TIM) in trypanosomes, showing that it contains two rhomboid-like proteins essential for protein import.